Population analysis of heavy metal and biocide resistance genes in Salmonella enterica from human clinical cases in New Hampshire, United States - Souza, Stephanie S. R.; Turcotte, Madison R.; Li, Jinfeng; Zhang, Xinglu; Wolfe, Kristin L.; Gao, Fengxiang; Benton, Christopher S.; Andam, Cheryl P. (Frontiers in Microbiology, 2022)
Microbes frequently encounter heavy metals and other toxic compounds generated from natural biogeochemical processes and anthropogenic activities. Here, we analyzed the prevalence and association of genes conferring resistance to heavy metals, biocides and antimicrobial compounds in 394 genome sequences of clinical human-derived S. enterica from New Hampshire, USA. The most prevalent was the gold operon (gesABC-golTSB), which was present in 99.2% of the genomes. In contrast, the other five heavy metal operons (arsenic, copper, mercury, silver, tellurite) were present in 0.76% (3/394) to 5.58% (22/394) of the total population. The heavy metal operons and three biocide resistance genes were differentially distributed across 15 sequence types (STs) and 16 serotypes. The number of heavy metal operons and biocide resistance genes per genome was significantly associated with high number of antimicrobial resistance genes per genome. Notable is the mercury operon which exhibited significant association with genes conferring resistance to aminoglycosides, cephalosporins, diaminopyrimidine, sulfonamide and fosfomycin. The mercury operon was co-located with the antimicrobial resistance genes aac(3)-IV, ant(3’’)-IIa, aph(3’)-Ia and aph(4)-Ia, CTX-M-65, dfrA14, sul1, and fosA3 genes within the same plasmid types. Lastly, we found evidence for negative selection of individual genes of each heavy metal operon and the biocide resistance genes (dN/dS < 1). Our study highlights the need for continued surveillance of S. enterica genotypes that carry those genes that confer resistance to heavy metals, biocides, disinfectants and other toxic compounds and that are often associated with mobile antimicrobial resistance genes. The selective pressures imposed by heavy metals and biocides on S. enterica may contribute to the co-selection and spread of antimicrobial resistance in human infections.